On the Strategic Use of Focal Points in Bargaining Situations - Maarten C.W. Janssen (Tinbergen Institute, 2006)
This paper argues that the notion of focal points is important in understanding bargaining processes. Recent literature confines a discussion of the usefulness of the notion to coordination problems and when bargaining experiments result in outcomes that are inconsistent with a straightforward interpretation of economic theory, some notion of `fairness' is invoked. This paper uses symmetry requirements to formalize the notion of focal points. By doing so, it explains the focality of equal split division and it re-interprets recent experimental evidence in bargaining games. Experimental economists should try to empirically disentangle the importance of focal points from other explanatory factors (such as fairness). One way to do so, would be to study modal (instead of average) responses more systematically. Future theoretical research should focus on the strategic implications of proposing a frame (focal point) to conceive of the bargaining problem.
Keywords: C78; C91; 330; Bargaining; Game Perceptions; Focal Points